2022
DOI: 10.3390/ma15114017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fiber Type and Length on Mechanical Properties of MICP-Treated Sand

Abstract: Fibers are applied in construction work to improve the strength and avoid brittle failure of soil. In this paper, we analyze the impact mechanism of fiber type and length on the immobilization of microorganisms from macroscopic and microscopic perspectives with fibers of 0.2% volume fraction added to microbial-induced calcite precipitation (MICP)-treated sand. Results show the following: (1) The unconfined compressive strength (UCS) of MICP-treated sand first increases and then decreases with increasing fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Tabakouei et al [57] said that the bridging effect of the fibers increases as the fiber length increases. According to Liang et al [58], their study reported that when exposed to an external force, the effect between fibers of different lengths and the soil takes different forms of failure. When the fiber length is short, the failure patterns are characterized by shearing or slipping of the fiber.…”
Section: The Effect Of Fiber Length On Soil Behaviormentioning
confidence: 99%
“…Tabakouei et al [57] said that the bridging effect of the fibers increases as the fiber length increases. According to Liang et al [58], their study reported that when exposed to an external force, the effect between fibers of different lengths and the soil takes different forms of failure. When the fiber length is short, the failure patterns are characterized by shearing or slipping of the fiber.…”
Section: The Effect Of Fiber Length On Soil Behaviormentioning
confidence: 99%
“…Different types of fibers have various surface physical properties, which will lead to different forms of contact between the fiber surface and the soil: a high surface roughness strengthens the interfacial friction between fibers and sand particles (Liang et al, 2022). The fiber content directly affects the three-dimensional mesh structure formed between fibers: additional fiber roots lead to a large contact area between fibers and sand particles, revealing a significant frictional effect in the MICP treated sand.…”
Section: Figurementioning
confidence: 99%
“…(8) e prepared culture medium and Sporosarcina pasteurii were put into a triangular flask and sealed with perforated plastic film, while they were placed in a constant temperature vibration incubator and shaken horizontally at the frequency of 150r • min −1 in order to expand the culture aerobically for 24 hours at 30 °C (see Figure 2(g)). (9) e Sporosarcina pasteurii solution cultured by step ( 8) was adjusted to OD � 1.5 by adding distilled water. In order to ensure that the experiment is carried out in a sterile environment, the above operations should be carried out on a sterile operation platform or on alcohol as much as possible.…”
Section: Bacteria and Culture Mediummentioning
confidence: 99%
“…However, the uniformity of the microbial cement-based material prepared by the preparation process in the same direction is worse than that of the microbial cement-based material prepared by the preparation process in different directions [8]. e results of Liang Shihua et al [9,10] show that for sand with good grain size distribution, the precipitation amount and the uniformity of calcium carbonate are better, and the porosity and permeability coefficient are smaller, which increased the unconfined compressive strength of the sample. Microbial-induced calcite precipitation could effectively improve the shear strength of granite residual soil as well as its internal friction angle and cohesion, Besides, the increase of cohesion was larger than that of the internal friction angle.…”
Section: Introductionmentioning
confidence: 99%